Analysis of the Leadership Style of HSE Managers in Construction Project Organizations (Case Study of Contractors in Construction Projects in Malang City) - Tarandima, Steevan Umbu Kawau; Negara, Kartika Puspa; Anwar, M. Ruslin (ASTONJADRO, 2025)
Continuous infrastructure development in Indonesia has become one of the factors increasing the role of the construction sector in the Indonesian economy. The construction sector's contribution to the Indonesian economy ranks sixth, at 9.88 percent of Indonesia's Gross Domestic Product (GDP) in the first quarter of 2024. The relatively high injury rate on construction projects is associated with construction workers facing ever-changing work environments, typically involving heavy machinery, working at heights, noise, and other serious hazards. To address these unique safety challenges, organizations must be able to quickly adapt to changes by effectively capturing, storing, and disseminating new strategies that prevent injuries. This can be achieved through the role of a leadership style that can exemplify the importance of occupational health and safety (HSE) management. Previous research results show that leaders who can implement leadership styles effectively and decisively enable workers to follow HSE procedures properly, thereby improving employee performance. In this research, questionnaires will be distributed to 3 contractor organizations in medium to large construction projects in Malang City. The scope of work analyzed is the leadership style. This research is a type of quantitative research. The visionary leadership style has a very high level of application, being the most dominant, followed by charismatic, transformational, and transactional leadership styles, which are applied at high levels, indicating that these leadership styles do not have a full influence.